SOFT POWER IN SYNTAX: THE SEMIOTICS OF MODERN DIPLOMATIC RHETORIC (Multidisciplinary Journal of Science and Technology, 2025)
This article examines four high-profile diplomatic speeches' linguistic, morphological, and paralinguistic features, emphasising their rhetorical construction, lexical choices, and performative strategies. Drawing on speeches delivered by Ambassador Scott C. Miller and a senior British diplomat, the study analyzes how political actors strategically blend formal rhetoric with emotional and symbolic language to promote national identity, reinforce international alliances, and sustain geopolitical legitimacy. By employing a comparative discourse analysis framework, the article situates these speeches within the broader contexts of contemporary soft power diplomacy and science diplomacy, highlighting the evolving nature of political communication in a globalised, media-driven world.